2014
DOI: 10.1111/jdv.12846
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is associated with combined allergic and irritant hand eczema, contact allergies and hyperhidrosis

Abstract: Our results reveal a predominance of smokers among patients with combined allergic and irritant hand eczema as well as with hyperhidrosis and relevant contact sensitizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 20 publications
1
30
1
4
Order By: Relevance
“…The three studies were performed on patch tested patients (43), on patients with chronic HE (44), and on patients with HE (45). For information regarding the correction for other risk factors, see Table 4.…”
Section: Results Of Other Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The three studies were performed on patch tested patients (43), on patients with chronic HE (44), and on patients with HE (45). For information regarding the correction for other risk factors, see Table 4.…”
Section: Results Of Other Studiesmentioning
confidence: 99%
“…The relationship between subclassification of HE and smoking was evaluated in five studies only (27,(42)(43)(44)(45); they found no significant association (42,45), a positive association with erythematous lesions and vesicles (27), a positive association with palmar eczema (43), or a positive association with combined irritant/allergic HE (44). However, HE is a heterogeneous disease: it may be that there are differences between the various subclasses of HE and factors such as smoking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that smokers are more likely to induce high airway reactivity, and allergic smoking [9] is also considered to be an important environmental factor contributing to asthma onset [10]. A survey found that tobacco consumption is on the rise around the world, at least a third of asthma patients were frequently exposed to a cigarette smoke environment [11].…”
Section: Introductionmentioning
confidence: 99%